Upaya Meningkatkan Hasil Belajar Menulis Teks Fabel Menggunakan Metode Contextual Teaching And Learning (Ctl) Dengan Media Kartu Pantun Siswa Kelas VII A SMP Negeri 2 Mertoyudan Tahun Pelajaran 2021/2022 - Munawaroh, Anik (Science and Education Journal (SICEDU), 2022)
One of the problems in learning Indonesian in the material for writing rhymes is the choice of words in writing sentences, especially to equate sounds. To overcome this problem, classroom action research (CAR) was carried out using the Contextual Teaching and Learning (CTL) learning method. The purpose of this study was to improve the learning outcomes of class VII A students of SMP Negeri 2 Mertoyudan the 2021/2022 academic year using the Contextual Teaching and Learning (CTL) learning model. The research subjects were 32 students, the source of research data was obtained from qualitative data in the form of data from observations of teacher and student activities and quantitative data in the form of test data on student learning outcomes. The results of the first cycle research were obtained by 27 students who completed with classical completeness of 84.37%. While the results of the second cycle of research increased with the number of students who completed as many as 32 students with a presentation of 100% completeness. Based on the results of this study, learning using the Contextual Teaching and Learning (CTL) can improve the learning outcomes of class VII A students of SMP Negeri 2 Mertoyudan the 2021/2022 academic year.